Palmprint identification protocol - Kadian, Siti Atikah (Universiti Sains Malaysia, 2016)
Palmprints, like fingerprints have unique features on it which can be utilised for identification process to verify or establish the identity of a person. They have features such as minutiae, pores, singular points, creases and wrinkles which remain immutable throughout lifetime. This project was conducted to find a reliable method for palmprint identification. In this project, the polygon method and the Gunn method were tested to see whether they are reliable method for palmprint identification. For the polygon method, 50 polygons were drawn on 50 palmprint images and polygons with similar shape were compared to see if the positions of the delta points and the length of each edges of the polygons are the same or not between the selected palmprint images. From these comparisons, it was found that most of the palmprints have different polygons shape and sizes due to different positions of the delta points on the palmprints. However, when using superimposition method, it was found that there were some palmprints that have similar shape and sizes of the polygons indicating that the positions of the delta points on the palmprints were similar. Hence, the polygon method may be useful in narrowing down possible palmprint for an unknown palmprint instead of using it for identification purpose. For the Gunn Method, it was applied to 50 palmprint images and the angles between the base line to each of the line of Gunn (Line A, B, C, D and E) and the length of each lines were compared between the palmprint images. It was found that all the readings are different between each palmprints. However, this method relies on features that are of class level as they are common for all human beings. Thus, it can be useful for classifying palmprints.